2021
DOI: 10.3390/jpm11020128
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Integrated Analysis of Insulin Resistance with Multi-Omics Data

Abstract: Technological advances in next-generation sequencing (NGS) have made it possible to uncover extensive and dynamic alterations in diverse molecular components and biological pathways across healthy and diseased conditions. Large amounts of multi-omics data originating from emerging NGS experiments require feature engineering, which is a crucial step in the process of predictive modeling. The underlying relationship among multi-omics features in terms of insulin resistance is not well understood. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…16 For example, Huang et al adopted a multiomics approach based on clinical features, proteomic, cytokines profile, microbiome and RNA-seq in order to identify 17 parameters able to distinguish insulin resistant (IR) and insulin sensitive subjects. 17 Choi and colleagues 12 included miRNAs profiling and proteome analysis on plasma samples of obese insulin resistant and lean subjects alongside with clinical features. The authors observed that decreased miR-24-3p and miR-495-3p expression and increased IGFBP5 and glycerol-3-phosphate dehydrogenase 1 (GPD1) proteins, are associated to peripheral insulin sensitivity and significantly distinguished insulin resistant from insulin-sensitive subjects.…”
Section: Introductionmentioning
confidence: 99%
“…16 For example, Huang et al adopted a multiomics approach based on clinical features, proteomic, cytokines profile, microbiome and RNA-seq in order to identify 17 parameters able to distinguish insulin resistant (IR) and insulin sensitive subjects. 17 Choi and colleagues 12 included miRNAs profiling and proteome analysis on plasma samples of obese insulin resistant and lean subjects alongside with clinical features. The authors observed that decreased miR-24-3p and miR-495-3p expression and increased IGFBP5 and glycerol-3-phosphate dehydrogenase 1 (GPD1) proteins, are associated to peripheral insulin sensitivity and significantly distinguished insulin resistant from insulin-sensitive subjects.…”
Section: Introductionmentioning
confidence: 99%